Basic life support and systems saving lives. Issue 6 (December 2021) - Olasveengen, Theresa Mariero; Semeraro, Federico
Abstract : Purpose of review: To describe recent science in basic life support (BLS) after cardiac arrest and how evolving knowledge in resuscitation is changing current guidelines and practices. Recent findings: The core elements of BLS have remained mostly unchanged since 2005 when Cardiopulmonary Resuscitation recommendations were changed from 2 ventilations to 15 compressions and up to three stacked shocks for shockable rhythms, to 30 compressions to 2 ventilations and single shocks. Since 2010, basic life support has largely focused on the importance of providing high-quality CPR for professional and lay rescuers alike. The most recent resuscitation updates has seen an increased focus on the systems perspective. The 'Systems Saving Lives' concept emphasizes the interconnection between community and Emergency Medical Services (EMS). The main changes in current resuscitation practice are within three important basic life support domains: recognition of cardiac arrest, interaction between rescuers and EMS and improving resuscitation quality. Summary: This review highlights the importance of strengthening both community and emergency medical services efforts to improve outcomes in cardiac arrest. Strategies that enhance the communication and collaboration between lay rescuers and professional resuscitation systems are important new avenues to pursue in developing systems that save more lives.